2020
DOI: 10.1111/ejn.14962
|View full text |Cite
|
Sign up to set email alerts
|

Impaired frontal‐parietal control network in chronic prostatitis/chronic pelvic pain syndrome revealed by graph theoretical analysis: A DTI study

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is characterized by chronic pain in pelvic area and lower urinary tract symptoms (LUTS). Previous neuroimaging studies demonstrated that chronic pain was associated with the altered brain activity. However, the pathological mechanisms associated with altered brain control of CP/CPPS are not well-understood. Therefore, we sought to investigate the topological properties of white matter brain networks in patients with CP/CPPS and whether the topological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Also, studies demonstrated that SC provides new insights into the understanding of chronic pain. For example, Huang et al (2021) found that patients with chronic prostatitis/chronic pelvic pain syndrome had alterations of SC within the frontal-parietal control network.…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies demonstrated that SC provides new insights into the understanding of chronic pain. For example, Huang et al (2021) found that patients with chronic prostatitis/chronic pelvic pain syndrome had alterations of SC within the frontal-parietal control network.…”
Section: Introductionmentioning
confidence: 99%
“…In their subsequent study using the same cohort, Takenaka et al found that decompression surgery increased ALFF in the superior frontal gyrus of CSM patients ( 9 ). Herein, we found a high across-voxel correlation between rCBF and FCS in the middle frontal gyrus of (CSM patients), a brain region that participates in processing chronic pain ( 67 , 68 ). The high neurovascular coupling may have resulted from the chronic pain in CSM patients.…”
Section: Discussionmentioning
confidence: 83%
“…The central nervous system functions to regulate excitation and inhibition, and the prefrontal cortex is a key region involved in the regulation of slow-moving pain and cognitive processing [8,9] . In fact, studies have con rmed the mechanism by which central regulation is feasible [10] , and imaging evidence has demonstrated that the long-term effects of chronic pain can cause gray matter density changes in regions such as the primary somatomotor cortex, primary somatosensory cortex, hippocampus and left amygdala [11] . Even these changes are not only related to pain production, but the occurrence of depression is signi cantly correlated with right hippocampal weight, but also the duration of pain, such as symptom duration of less than 7.5 years was signi cantly related to left amygdala [12,13] .…”
Section: Introductionmentioning
confidence: 99%